Uji Pemanfaatan Rhizobia Sp. Dalam Meningkatkan Kadar Fosfat Tanah Dan Serapan Fosfat Tanaman Kedelai - M Reza Alfikri (Peneliti.net, 2023)
Phosphate is an essential nutrient for plant growth and development. However, most of the phosphate in the soil is in a form that is not directly available to plants. In increasing the availability of phosphate in the soil, more environmentally friendly microbes such as Rhizobia sp. One interesting approach is through the interaction between plants and bacteria Rhizobia sp. Recent research has shown that Rhizobia sp. can also have an important role in increasing the utilization of phosphate by plants. Rhizobia sp has the ability to produce phosphatase enzymes. The role of Rhizobia sp in increasing the utilization of phosphate in plants, it is hoped that more effective methods can be found in increasing the availability of phosphate and optimizing the use of phosphate resources in agriculture. The purpose of this research is to understand in depth the role of Rhizobia sp in increasing the utilization of phosphate by plants. This research was conducted at the Experimental Field of the Nusantara Technology University. The research method used in this study was a randomized block design with 2 variables, namely liming and isolates of Rhizobia sp. The results showed that the application of Rhizobia sp isolate had a significant effect on P levels and P uptake of soybean plants. Isolate Rhizobia sp. the best was treatment I9 (BGR 3), thus the isolate was effective in increasing the availability of phosphate and could be absorbed by plants effectively. Giving Rhizobia sp can increase phosphorus indirectly due to interactions between plants and Rhizobia sp. which produces the enzyme phosphatase.